International Conference on Biomedical and Health Informatics ICBHI 2015, Haikou, China, 8-10 October 2015 - Zhang, Yuan-Ting; Carvalho, Paulo; Magjarevic, Ratko (IFMBE Proceedings, 2019)
This volume presents the proceedings of the International Conference on Biomedical and Health Informatics (ICBHI). The conference was a new special topic conference and a common initiative by the International Federation of Medical and Biological Engineering (IFMBE) and IEEE Engineering in Medicine and Biology Society (IEEE- EMBS). BHI2015 was held in Haikou, China, 8-10 October 2015. The main theme of the BHI2015 is "The Convergence: Integrating Information and Communication Technologies with Biomedicine for Global Health". The ICBHI2015 proceedings examine enabling technologies of sensors, devices and systems that optimize the acquisition, transmission, processing, storage, retrieval, use of biomedical and health information as well as to report novel clinical applications of health information systems and the deployment of m-Health, e-Health, u-Health, p-Health and Telemedicine. .